The impact of demographic and individual heterogeneity on unemployment duration: A regional study - William Collier (University of Kent, Department of Economics, 2003)
This paper investigates the impact of individual heterogeneity and regional influences on unemployment duration utilising cross-section microeconomic data drawn from a representative random survey of individual job seekers for the English County of Kent. These individual-level data are unique in that they provide information concerning the personal characteristics of job seekers, alongside direct observations of both their reservation wages and job search behaviour. Such data are extremely rare and, to our knowledge, have never before been utilised in a regional context. Thus, the paper contributes to the empirical literature by analysing the extent to which individual heterogeneity and intra-regional variation in labour market opportunities impact upon the observed distribution of unemployment duration(s). This is an important issue for policy formation and the results provide new insights into the benefits of current policies aimed at increasing the employability of the unemployed.
Keywords: C21; C31; J64; R10; 330; Unemployment Duration; Job Search; Regional Labour Markets; Arbeitslosigkeit; Dauer; Arbeitsuche; Regionale Disparität; Großbritannien